Provenance influences seed germination and phenotypic responses to water restriction in the endemic Beilschmiedia miersii (Gay) Kosterm - Magni, Carlos R.; Poch, Paola L.; Espinoza, Sergio E.; Yáñez, Marco A.; Martínez, Eduardo E.; Promis, Alvaro A.; Mancilla, Gabriel A. (Frontiers in Forests and Global Change, 2023)
The higher drought intensity recorded in the last decades in the Mediterranean zone of Chile increased the level of threats of the endemic Beilschmiedia miersii (Gay) Kosterm and has raised concern about its capacity to face drought. In this study, we assessed the effect of seed provenance and mother tree on seed germination traits, seedling growth, biomass allocation, presence of cotyledons, and survival responses of B. miersii cultivated under two water treatments (well-watered versus water stress. Average pre-dawn plant water potentials of −0.9 and −4.5 MPa, respectively). The germination stage of this trial showed significant differences in germination capacity, germination energy, and the maximum value of Czabator. Provenances from the southern range of the species, with higher precipitation (Cantillana and El Arbol) had a better germination performance, however, once germinated, the ability of the seedlings to survive in the nursery was high only in two of the five provenances under study. The coastal and interior provenances with lower precipitations (El Pobre, Longotoma, and Antumapu) were not able to survive to the seedling stage (<5% survival). Seedling growth and survival varied significantly between the two remaining provenances and the two watering treatments. The provenance El Arbol, exhibited a higher survival, growth, presence of cotyledons, and biomass traits. This provenance also exhibited a higher presence of cotyledons in both watering treatments and an unaltered root to shoot ratio between the well-watered and the water stress treatments. Our results suggests that there is important phenotypic variation for seed germination and seedling survival associated to the provenance origin, emphasizing the importance of a nursery-evaluation phase before the beginning of restoration projects at the landscape level.